Fire safety questions and answers a practical approach - Perry, Pat, 1954- (Thomas Telford, 2003)
Pat Perry's guide to fire risk assessment and prevention in the work place is both practical and comprehensive. Fire safety legislation has been under scrutiny for quite some time and a new approach is anticipated during 2004 placing a much greater emphasis on self-regulation by employers.